SIFAT PEMESINAN 32 JENIS KAYU DARI DAERAH JAWA BARAT DAN NUSA TENGGARA TIMUR - Osly Rachman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The paper presents a test result of machining properties of 32 wood species from West Java and East of Nusa Tenggara East. The air dried samples were tested according to the ASTM D1666/64 standard that was modified according to the Forest Products Research Institute Report No. 160 (1982). In most of the species 25 or more samples were available for test. The machining properties tested included planning, shaping, boring, turning and sanding.The result reveals that eighteen wood species have good to very good machining properties, five species have very good machining properties namely gintung, pongokan, rasamala, melur, tanjung and leda II.The other species are good or fair in some properties and poor or very poor in other. The species with poor or very poor machining properties are bareuhbeuy, hantap heulang and leda III.